Microplastics dysregulate innate immunity in the SARS-CoV-2 infected lung - Bishop, Cameron R.; Yan, Kexin; Nguyen, Wilson; Rawle, Daniel J.; Tang, Bing; Larcher, Thibaut; Suhrbier, Andreas (Frontiers in Immunology, 2024)
A growing body of clinical data shows an association between exposure to microplastic (MP) pollution and increased severity of respiratory infections. Global MP pollution is now well recognized, with humans and animals consuming and inhaling MPs on a daily basis. Using a mouse model of mild COVID-19, we described herein the effects of azide-free, 1 µm polystyrene MP beads co-delivered into lungs with a SARS-CoV-2 omicron BA.5 inoculum. Although infection reduced clearance of MPs from the lung, virus titres and viral RNA levels were not significantly affected by MPs, and overt MP-associated clinical or histopathological changes were not observed. However, RNA-Seq of infected lungs revealed that MP exposure suppressed innate immune responses at 2 days post infection (dpi) and increased pro-inflammatory signatures at 6 dpi. The cytokine profile at 6 dpi showed a significant correlation with the 'cytokine release syndrome' signature observed in some COVID-19 patients. The findings are consistent with the recent finding that MPs can inhibit phagocytosis of apoptotic cells via binding of Tim4. They also add to a growing body of literature suggesting that MPs can dysregulate inflammatory processes in specific disease settings.